Mechanism of sulfur vacancies and doping in 1 T'-MoS2 toward the evolution of hydrogen - Zhou, Jing; Chen, Junyu; Chen, Shuxuan; Wu, Yu; Cao, Jiamu; Zhang, Yufeng (Chemical physics letters, 2022)
[Display omitted] •1. Revealed the mechanism of HER on doped-1 T' MoS2 and S-defect 1 T' MoS2.•2. Studied the optimization mechanism of appropriate doping for HER on 1 T' MoS2.•3. Found Ni doping could make up for the negative effect brought by S defects.•4. Provided theoretical basis for MoS2-based materials on HER applications. Due to the high activity, MoS2 is promising in replacing Pt-based electrocatalysts in hydrogen evolution reaction (HER) applications. However, the poor conductivity and fewer activity sites of 2H-MoS2 impede its practical application. The overall performance of 1 T'-MoS2 still has gaps to those Pt-based electrocatalysts. Thus, in this work, methods of doping and introducing defects were attempted to further improve the HER performance of 1 T'-MoS2. Through first-principle methods, the mechanism of HER on 1 T'-MoS2 with dopants or defects was analyzed. We found that Ni doping can further optimize the HER performance of 1 T'-MoS2.